2020
DOI: 10.33988/auvfd.674702
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Turkish honey against selected foodborne pathogens

Abstract: Honey is an important animal product that is consumed by people of all ages and has become an important antimicrobial agent because it has both antibacterial properties and does not cause microbial resistance. Although, Turkey is among the most important honey producers of the world, there are not enough studies about the antibacterial activity of Turkish honey. According to their geographical area, honey exhibit considerable and variable antimicrobial activity. In this study, we investigated the in vitro anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…By examining both graphs, it can be observed that the honeys exhibited distinct antimicrobial effects against the selected food pathogens. This finding supports the results obtained by other researchers (Çakır and Dervişoğlu, 2022;Hulea et al,2022;İplikçioğlu-Çil et al,2020;Yalazi and Zorba,2020).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…By examining both graphs, it can be observed that the honeys exhibited distinct antimicrobial effects against the selected food pathogens. This finding supports the results obtained by other researchers (Çakır and Dervişoğlu, 2022;Hulea et al,2022;İplikçioğlu-Çil et al,2020;Yalazi and Zorba,2020).…”
Section: Resultssupporting
confidence: 93%
“…Flower origin, colour, aroma and taste are important factors in determining the quality of honey (Piana et al,2023). In addition to being an important animal product, honey has become an important antimicrobial food because it has antibacterial properties and does not cause microbial resistance (Acaroz et al,2024;Asma et al,2022;İplikçioğlu-Çil et al, 2020). There is great interest in destroying foodborne pathogens or preventing their multiplication in food (Çakmak et al,2023;İplikçioğlu-Çil et al,2020;Schell et al,2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance at the maximum absorption wavelength (441 nm) of the supernatant was measured, and the loading capacity of SPEO-Ms was calculated according to the drawn standard curve. The embedding rate was calculated by Equation (2) [39], and the experiment was repeated three times. The average value was used as the final result.…”
Section: Determination Of Speo-m Encapsulation Efficiencymentioning
confidence: 99%